Democratic Republic of the Congo : Second Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2003)
For the past two years, the Democratic Republic of Congo has made considerable progress in consolidating its peace process, stabilizing its economic situation, and creating the conditions for sustainable economic growth and poverty reduction. The macroeconomic and fiscal performances under the IMF program were satisfactory. The government also made good progress on structural and sectoral reforms. The authorities have identified the key steps needed for the completion of the poverty reduction strategy paper. The IMF staff commends the authorities for the progress achieved in strengthening the tax and customs administration.